Réponses

2013-03-08T17:51:44+01:00

1- (2x - 3)² -( 1 -4x)(2x-3)
= 4x² -12x + 9 -(2x -3 -8x² +12x)
= 4x² -12x + 9 -2x +3 +8x² - 12x
= 12x² -26x +12 

2- 12 *0² - 26*0+12
=12

3- 12* (3/2)² - 26 * 3/2 +12
= 0
p.s: le signe * est fois

2013-03-08T17:59:49+01:00

E= (2x-3)² - (1-4x)(2x-3)

= (2x)² + 3² - 2(2x)(3) - [2x -3 -8x² +12x]

= 4x² +9 -12x -2x +3 +8x² -12x

= 12x² -26x +12

 

Si x = 0

E= 12(0)² -26(0) +12

= 12

 

Si x=3/2

E= 12(3/2)² -26(3/2) +12

= 12(9/4) -13(3/1) +12

= 3 x 9 - 13 x 3 + 12

= 27 - 39 + 12

= 0